International Agreements in Law at Health Sector of the Republic of Uzbekistan - Azkhodjaeva, R. (Asian Pacific Journal of Environment and Cancer, 2021)
This article examines international legal documents and national legislation of Uzbekistan in the in the health protection sphere, the activities of the United Nations, analyzes international legal documents regulating health protection issues, cooperation of the Republic of Uzbekistan in the field of health protection.